2013
DOI: 10.1159/000354889
|View full text |Cite
|
Sign up to set email alerts
|

Azelaic Acid in the Treatment of Acne in Adult Females: Case Reports

Abstract: Acne, one of the most common skin problems in dermatological practice, is a condition that affects not only adolescents but also adults. While approximately 80% of cases occurring in adulthood are persistent from teenage years, around 20% are described as ‘late-onset' disease, appearing for the first time in adulthood. The disease can be triggered by hormonal changes (including a change from one contraceptive to another), or it can be induced by certain nonhormonal medications, emotional stress, and various un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…‘Acne tarda’ is predominantly characterized by a mild to moderate severity with many inflammatory lesions, frequently involving the lower third of the face, the so‐called ‘U‐zone’ . Approximately 20% women affected, report a ‘late‐onset acne’ which developed after the age of 25 years .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…‘Acne tarda’ is predominantly characterized by a mild to moderate severity with many inflammatory lesions, frequently involving the lower third of the face, the so‐called ‘U‐zone’ . Approximately 20% women affected, report a ‘late‐onset acne’ which developed after the age of 25 years .…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 20% women affected, report a ‘late‐onset acne’ which developed after the age of 25 years . However, the majority of adult female acne patients suffer from persistent (continuous from adolescence onwards) acne, making them a vulnerable population to the negative impact of their skin condition to quality of life (QoL) . Especially, acne tarda is associated with lower self‐esteem, anxiety in social interaction and stigmatization due to imperfect appearance which causes distress, predominantly in female adult patients resulting in a negative impact on QoL …”
Section: Introductionmentioning
confidence: 99%
“…In a split‐face clinical trial, a lotion containing Myrtus communis was shown to be effective and safe for the treatment of mild to moderate acne vulgaris 11 . Azelaic acid has been shown to be effective in treating and maintenance treatment of acne by reducing acne lesions, decreasing the amount of secreted sebum, as well as alleviating PIH 12–16 . The aim of our exploratory study was to evaluate the efficacy of the test product containing these two anti‐acne ingredients compared with a light moisturizing cream in adult females in acne maintenance phase.…”
Section: Test Product Group Comparative Product Groupmentioning
confidence: 99%
“…Soon after, by a soft massage and the use of a light LED device, it has been possible to remove and modulate more easily both FFA and dead cells from clogged pores, increasing also the penetration of the emulsion's active ingredients [22]. An emulsion based on chitin-lignin micro/nanoparticles entrapping niacinamide [23][24][25][26], phosphatidylcholine [27,28] and azelaic acid [29], was applied together with a water solution of specific plant's active compounds, such as Chirthmum maritimum and the witch/hazel extracts [30]. The same home treatments and the use of the sunscreen are mandatory for all.…”
Section: Anti-acne Treatmentmentioning
confidence: 99%